Revisión de la literatura de la logística inversa - Ocio Guevara, Andrea Mireille (2021)
The present research article corresponds to an in-depth investigation of several articles on reverse logistics by researchers from different countries, such as Cuba, Denmark, Iran, Brazil, among others. Its advantages, disadvantages, as well as its evolution over time are detailed. The perception from the point of view of companies and customers. Also, how it is related to other concepts such as sustainability, closed supply chain, social responsibility, circular economy, sustainable management, product life cycle, value to management, among others. It also mentions certain reuse, remanufacturing, recycling, repair, and disposal strategies. Finally, its vision for the future in first and third world countries and how to manage it in order to have benefits and a good perception from customers.